The Role of the Glyoxylate Shunt in the Acclimation to Iron Limitation in Marine Heterotrophic Bacteria - Koedooder, Coco; Guéneuguès, Audrey; Van Geersdaële, Rémy; Vergé, Valérie; Bouget, François-Yves; Labreuche, Yannick; Obernosterer, Ingrid; Blain, Stéphane (Frontiers in Marine Science, 2018)
Iron (Fe) is an essential element for marine microbial growth but is present in trace amounts (<0.1 nM) in surface waters of the ocean. In heterotrophic bacteria, Fe-limitation particularly impacts ATP production as Fe is an essential co-factor of enzymes involved in the electron-transport chain as well as the tricarboxylic acid (TCA) cycle. Fe-limitation can therefore drastically reduce both bacterial growth and respiration, consequently affecting the efficiency of organic carbon remineralization. Heterotrophic bacteria possess various strategies to cope with Fe-limitation. In the present study we tested the hypothesis that the induction of the glyoxylate shunt can represent one such strategy. Genetic approaches were used to gain insight into the potential role the glyoxylate shunt may have in alleviating Fe-stress using the gammaproteobacterium Photobacterium angustum S14. A recombinant bioluminescent reporter of P. angustum S14 (icl-luc) revealed a strong and significant increase in icl expression when cells were subjected to strong Fe-limitation. Although both the growth and respiration rates decreased for the wildtype and an isocitrate lyase knockout mutant (∆icl) under strong Fe-limitation, they were ±30% lower for ∆icl as compared to the wildtype. Complementation of ∆icl restored the growth and respiration rates to those observed in the wild type, further confirming the importance of the glyoxylate shunt under strong Fe-limitation. Due to the ubiquitous nature of the glyoxylate shunt within marine bacteria, our results lead us to propose this pathway as an important acclimation strategy for marine heterotrophic bacteria that are subjected to Fe-limitation.